The Isolation and Characterisation of Seco-phthalide Isoquinoline Alkaloid from Corydalis species - Jha, Ram Narayan (Journal of Nepal Chemical Society, 2013)
Chromatographic resolution of crude base fraction of the methanolic extract of the whole plant of Corydalis longipes on Silca-gel column yielded one Seco-phthalide isoquinoline alkaloid, N-methylhydrasteine hydroxyl lactam. Its structure was established on the basis of extensive spectroscopic data analysis and comparison with spectroscopic data reported. DOI: http://dx.doi.org/10.3126/jncs.v30i0.9389 Journal of Nepal Chemical Society Vol. 30, 2012 Page: 165-167 Uploaded date: 12/20/2013